Cognitive effects of aromatase inhibitors in early breast cancer patients: a prospective study - Giuffrè, Guido Maria; Carbognin, Luisa; Masone Iacobucci, Giovanna; Gistro, Maria; Tanzilli, Antonio; Morganti, Valentina; Fuso, Paola; Raffaele, Mimma; Rossi, Valentina; Paris, Ida; Palazzo, Antonella; Corsi, Domenico Cristiano; et al. (Breast cancer research and treatment, 2025)
Purpose Several patients undergoing aromatase inhibitors (AIs) for breast cancer (BC) report cognitive difficulties, although studies on the cognitive effects have yielded mixed findings. This prospective study aimed to investigate the impact on cognitive function of adjuvant AIs and the changes over time. Methods Patients with diagnosis of early-stage BC, eligible for adjuvant AIs endocrine therapy, underwent comprehensive neuropsychological assessments for the evaluation of several cognitive domains before and after 12 months of therapy. Participants were stratified according to menopausal status, type of surgery, and prior chemotherapy. Results Eighty-three subjects were enrolled and, among these, 77 patients underwent neuropsychological assessments. At baseline, post-menopausal subjects (71%) performed significantly worse than pre-menopausal subjects in tests assessing executive functions. Subjects who received chemotherapy were younger, but showed poorer episodic memory performance compared to those chemotherapy-naïve. After 12 months, although most patients (66.1%) reported cognitive difficulties, the neuropsychological performance did not show significant deterioration. Notably, differences in verbal episodic memory between subjects treated with or without chemotherapy persisted over time. Conclusion This study suggests that the cognitive difficulties reported by BC patients who underwent AIs may be more influenced by prior chemotherapy rather than from the direct cognitive effects of AIs, highlighting the persistent cognitive consequences of chemotherapy. These findings emphasize the need for further research to better understand the interplay between chemotherapy, AIs, and cognitive function and the relevance of cognitive assessments.